Keutamaan Kemampuan Berbahasa Inggris untuk Industri Pariwisata Terintegrasi Kearifan Lokal - Juriana, Juriana; Tujuh, Syarifah HR DG; Dewi, Ratna (LENTERNAL: Learning and Teaching Journal, 2023)
The Bangka Belitung tourism industry is integrated with local wisdom and has the ability to become an international tourism industry by involving all stakeholders, such as the government, the private sector and the community. local government policies determine the direction of the Bangka Belitung tourism industry. Some advantages of English in the tourism industry are integrated with local wisdom, namely 1) to support the advancement of the tourism industry, 2) to facilitate communication in problem solving, greetings, exchange of information, more precise location indicators, buying and selling of goods or services, and others, 3 ) to minimize misinterpretation of words or sentences that occur in conversations with both local and foreign tourists, and 4) make it easier for foreign tourists to recognize Bangka Belitung with the characteristics (local brand) owned by the province. As for various types of tourism in the area, such as cultural tourism, marine tourism, and culinary tourism. This research is a literature study related to the tourism industry, English, and local wisdom. Abstrak Industri pariwisata Bangka Belitung bisa menjadi industri pariwisata bertaraf internasional dengan melibatkan semua stakeholder yaitu pemerintah, swasta, dan masyarakat. kebijakan pemerintah daerah sangat menentukan arah industri pariwisata Bangka Belitung sehingga bisa meningkatkan Pendapatan Asli Daerah. Dalam bidang pelayanan, Bahasa Inggris sangat diperlukan sehingga perlu menghubungkan Bahasa Inggris tentang pariwisata yang terintegrasi dengan kearifan lokal. Selain untuk pelayanan, juga bisa mempromosikan semua jenis wisata yang ada agar wisatawan asing merasa senang berkunjung dan menikmati liburan mereka dengan sukacita. Kearifan lokal juga sangat diperlukan untuk meminimalisir permasalahan yang terjadi seperti kesalahan makna dalam penggunaan bahasa ketika para wisatawan berkunjung, baik wisatawan lokal maupun asing. Penelitian ini merupakan studi literatur yang berkaitan dengan industri pariwisata, Bahasa Inggris, dan Kearifan Lokal.